Protective effect of compatible herbs in Jin-Gu-Lian formula against Alangium chinense-induced neurotoxicity via oxidative stress, neurotransmitter metabolisms, and pharmacokinetics - Lian, Dongyin; Chen, Tengfei; Yan, Lihua; Hou, Hongping; Gao, Shuangrong; Hu, Qin; Zhang, Guangping; Li, Han; Song, Ling; Gao, Yunhang; Pu, Yunxi; Chen, Ying; et al. (Frontiers in Pharmacology, 2023)
Background: Alangium chinense frequently used in Miao medicine to treat rheumatic diseases. However, as a famous toxic herb, A. chinense and its representative components exhibit ineluctable neurotoxicity, thus creating significant challenges for clinical application. The combined application with compatible herbs in Jin-Gu-Lian formula attenuates such neurotoxicity according to the compatible principle of traditional Chinese medicines. Purpose: We aimed to investigate the detoxification of the compatible herbs in Jin-Gu-Lian formula on A. chinense-induced neurotoxicity and investigate its mechanism. Methods: Neurobehavioral and pathohistological analysis were used to determine the neurotoxicity in rats administered with A.chinense extract (AC), extract of compatible herbs in Jin-Gu-Lian formula (CH) and combination of AC with CH for 14 days. The mechanism underlying the reduction of toxicity by combination with CH was assessed by enzyme-linked immunosorbent assays, spectrophotometric assays, liquid chromatography tandem-mass spectrometry and real-time reverse transcription-quantitative polymerase chain reaction. Results: Compatible herbs attenuated the AC-induced neurotoxicity as evidenced by increased locomotor activity, enhanced grip strength, the decreased frequency of AC-induced morphological damage in neurons, as well as a reduction of neuron-specific enolase (NSE) and neurofilament light chain (NEFL) levels. The combination of AC and CH ameliorated AC-induced oxidative damage by modulating the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), and total antioxidant capacity (T-AOC). AC treatment significantly reduced the levels of monoamine and acetylcholine neurotransmitters in the brains of rats, including acetylcholine (Ach), dopamine (DA), 3,4-dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA), norepinephrine (NE), and serotonin (5-HT). Combined AC and CH treatment regulated the abnormal concentrations and metabolisms of neurotransmitters. Pharmacokinetic studies showed that the co-administration of AC and CH significantly decreased plasma exposure levels of two main components of AC, as evidenced by the reduction of maximum plasma concentration (Cmax), area under the plasma concentration-time curve (AUC) compared to AC. In addition, the AC-induced downregulation in mRNA expression of cytochrome P450 enzymes was significantly reduced in response to combined AC and CH treatment. Conclusion: Compatible herbs in Jin-Gu-Lian formula alleviated the neurotoxicity induced by A. chinense by ameliorating oxidative damage, preventing abnormality of neurotransmitters and modulating pharmacokinetics.